DINAMIKA DIRI DALAM SENI LUKIS KONTEMPORER - RAHMAT, Yasrul Sami, S.Sn., M.Sn., Dra. Jupriani, M.Sn. (Serupa The Journal of Art Education, 2019)
The creation of this final work aims to visualize things related to self dynamics and identify forms related to self dynamics. The creation method in this final work uses five stages, namely the preparation stage, the elaboration stage, the synthesis stage, the realization phase of the concept and the completion stage, and is closed by holding an exhibition of paintings. This work uses acrylic paint and oil paint media with brush stroke techniques and uses colors that match the object using contemporary realist patterns. This work tells about self changes, departing from the problems or problems that are experienced then impacting on the changing personality.Kata kunci : perubahan diri, seni lukis.